2004
DOI: 10.1007/s00467-004-1619-5
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-?1 in nephrotic syndrome treated with cyclosporine and ACE inhibitors

Abstract: The aim of the study was to assess urinary transforming growth factor (TGF)-beta1 in children with steroid-dependent nephrotic syndrome (SDNS) treated with cyclosporine A (CyA) and ACE inhibitors (ACEI). The study involved 24 children (14 boys and 10 girls) with SDNS and signs of focal segmental glomerulosclerosis. The children were treated with prednisone, CyA, and ACEI. All children were examined four times: A during relapse of proteinuria, before treatment with CyA and ACEI, and B after 3 months, C 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Increased urinary TGF-beta is detected in patients with some forms of nephrotic syndrome (6), IgA nephropathy (7), and focal segmental glomerulosclerosis (FSGS) (7, 8). Interestingly, while detection of TGF-beta in the urine can differentiate between FSGS and the non-fibrotic process of minimal change disease (8), TGF-beta levels cannot be used predict response to corticosteroid therapy, despite the fact that some anti-fibrotic treatments may reduce these levels (9). In human FSGS (10) and in experimental models of renal fibrosis (11), TGF-beta is closely associated with ECM accumulation.…”
Section: Tgf-beta and The Pathogenesis Of Chronic Kidney Diseasementioning
confidence: 99%
“…Increased urinary TGF-beta is detected in patients with some forms of nephrotic syndrome (6), IgA nephropathy (7), and focal segmental glomerulosclerosis (FSGS) (7, 8). Interestingly, while detection of TGF-beta in the urine can differentiate between FSGS and the non-fibrotic process of minimal change disease (8), TGF-beta levels cannot be used predict response to corticosteroid therapy, despite the fact that some anti-fibrotic treatments may reduce these levels (9). In human FSGS (10) and in experimental models of renal fibrosis (11), TGF-beta is closely associated with ECM accumulation.…”
Section: Tgf-beta and The Pathogenesis Of Chronic Kidney Diseasementioning
confidence: 99%
“…Consistently, among our patients, baseline TGF‐β1 excretion was higher among those who underwent dialysis and also correlated well with the severity of the acute renal damage. Other authors have already reported a significant correlation between TGF‐β1 urinary levels and the magnitude of the proteinuria and the GFR drop . Activation of the TGF‐β1 axis explains many morphological alterations in chronically failing kidneys .…”
Section: Discussionmentioning
confidence: 93%
“…In patients with primary and secondary glomerulopathies, renal glomeruli contain a few times more mRNA TGF-β1 than in healthy subjects [40,41]. Wasilewska and ZochZwierz found that urinary TGF-β1 level increased in proportion to proteinuria during relapse of NS [42]. Zhang et al showed an increase in TGF-β1 expression in the kidneys of rats with adriamycin-induced nephropathy which was prevented by simvastatin [43].…”
Section: Discussionmentioning
confidence: 95%